1905 : suivi de bilan et perspectives - Trotski, Leon; Parijanine, Maurice; Bloch, Gérard (Paris : Editions de Minuit, 1969)
Bibliotheek François Vercammen
Frans
Monografie
Keywords: Russische Revolutie 1905